Study of the topographic and optical properties of gold metal nanomaterial’s prepared with three pulses laser (300,500,700) - Atyaf Sarhan Farhan Alrubaie (Genius Journals, 2023)
The gold nanoparticles were prepared. With ionic water laser ablation using an (Nd: Yag) laser with a wavelength of 532 nm and energy (90mJ) using three different laser pulses (300, 500, and 700), deionized liquid water was used. The crystalline nature has been studied through an X-ray diffraction device, and the results showed that gold nanomaterial has the cubic structure (FCC); As for the surface, terrain prepared. It was studied using an atomic force microscope. It was found that the increase in the number of laser pulses led to the rise in the large nanoparticles resulting from the agglomeration of small nanoparticles, thus increasing the average size of the NPS. As for the optical properties of colloidal gold nanoparticles, they were studied using the absorption spectra at wavelength range (300-1100) nanometer where an increase in absorbance was observed with a decrease in transmittance and an increase in the number of laser pulses, as well as a reduction of the value of the light energy gap.
Keywords: Gold nanoparticle; Double distilled and deionized water